2019
DOI: 10.1101/510164
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Modulation of tonotopic ventral MGB is behaviorally relevant for speech recognition

Abstract: Impact statement: Ultra-high field neuroimaging dissects the ventral medial geniculate 17 body (vMGB) of the primary auditory pathway from other MGB subregions and reveals that 18 vMGB top-down modulation is relevant for speech recognition. Abstract 23Sensory thalami are central sensory pathway stations for information processing. Their role for human 24 cognition and perception, however, remains unclear. Recent evidence suggests an involvement of the 25 sensory thalami in speech recognition. In particular, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
22
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
2
1

Relationship

5
0

Authors

Journals

citations
Cited by 5 publications
(25 citation statements)
references
References 161 publications
(149 reference statements)
2
22
1
Order By: Relevance
“…A task-dependent modulation for speech recognition means that sensory thalamus responses were higher for speech tasks (that emphasized recognition of fast-varying speech properties) in contrast to control tasks (that required recognition of relatively constant properties of the speech signal, such as the speaker identity or the sound intensity level). The studies also found that the performance level in auditory speech recognition was positively correlated with the task-dependent modulation in the MGB of the left hemisphere (von Kriegstein, Patterson, and Griffiths 2008;Mihai et al 2019).…”
Section: Introductionmentioning
confidence: 87%
See 4 more Smart Citations
“…A task-dependent modulation for speech recognition means that sensory thalamus responses were higher for speech tasks (that emphasized recognition of fast-varying speech properties) in contrast to control tasks (that required recognition of relatively constant properties of the speech signal, such as the speaker identity or the sound intensity level). The studies also found that the performance level in auditory speech recognition was positively correlated with the task-dependent modulation in the MGB of the left hemisphere (von Kriegstein, Patterson, and Griffiths 2008;Mihai et al 2019).…”
Section: Introductionmentioning
confidence: 87%
“…From Wernicke's research (Wernicke 1874) all the way up to current findings, neuroscientific models of speech recognition have mostly focused on cerebral cortex mechanisms (Hickok and Small 2015;Friederici and Gierhan 2013). Recent findings, however, suggest that a full understanding of speech recognition mechanisms is impossible without understanding cerebral cortex feedback mechanisms to the subcortical sensory pathways (von Kriegstein, Patterson, and Griffiths 2008;Diaz et al 2012;Dí az, Blank, and von Kriegstein 2018;Mihai et al 2019;Chandrasekaran et al 2009;Chandrasekaran, Kraus, and Wong 2011), in particular, to the sensory thalami (von Kriegstein,et al 2008;Diaz et al 2012;Dí az et al 2018;Mihai et al 2019).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations